Local attachment ventilation system for the unearthed relic preservation area within site museum. (February 2022) - Dang, Yuexi; Luo, Xilian; Chang, Bin; Huang, Xingyu; Feng, Zhuangbo; Gu, Zhaolin
Highlights: Promising HVAC system for confined preservation areas in site museum. Local environmental control system for relics in large space exhibition hall. Using intrinsic soil parameters as the setpoints of environmental control was promoted. Abstract: Environmental control of relic preservation areas in site museums with large exhibition halls is attracting growing interest. Local environmental control systems, such as displacement ventilation, can provide a suitable preservation environment in these museums with low energy consumption. However, the positioning of the air supply inlet at the bottom of the preservation area is not always feasible, because historical sites generally comprise the entire excavation area. This study proposes the use of an attachment ventilation system, which installs the air inlet and outlet at the top of opposite walls, as a more effective local environmental control system for the preservation of unearthed relics in funerary pits. Experiments were conducted in an experimental exhibition hall to evaluate the feasibility of this system. The diurnal temperature fluctuation of the preservation area decreased from 4.5 ℃ when the system was off to 1.7 ℃ when the system was on, and the corresponding temperature difference between the surrounding soil and air of relics decreased from 1.6 °C to 0.3 °C, thereby establishing a stable soil–air environment. These results demonstrate that attachment ventilation is an effective local environmental control strategy for the preservation of unearthed relics in site museums.